Research on interference avoidance detection method for wireless access system - Jian GONG; Xu SHI; Qiaochun XU (Dianxin kexue)
The types of interference avoidance mechanisms adopted by wireless access systems to realize spectrum sharing and compatibility were introduced, and the specific detection methods such as channel occupancy time, idle channel evaluation, idle channel evaluation time cumulative probability distribution statistics, determination of interference signal detection threshold, silent period duration and equivalent utility were explained.The problems in the actual device detection system were highlighted, and new effective channel occupancy time and idle channel evaluation algorithms and the determination process were given.